2022
DOI: 10.1016/j.ufug.2022.127492
|View full text |Cite
|
Sign up to set email alerts
|

Urban green spaces and stress during COVID-19 lockdown: A case study for the city of Madrid

Abstract: Due to the unexpected emergence of COVID-19, different cities improvised responses to prevent the virus from spreading and infecting the population. Madrid, capital of Spain and one of the most affected cities in Europe, confined everyone home and closed most public and private spaces, including public parks. The whole situation was surely to be responsible for stress-levels to peak. We developed an online survey to better understand the relationship between people and Urban Green Spaces prior to the COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 47 publications
(72 reference statements)
1
24
0
1
Order By: Relevance
“…The specific characteristics of the environment during the pandemic were far less important than the opportunities for outdoor activity that they afforded. For instance, other studies mentioned that most first-time users reported that having access to outdoor spaces during COVID-19 was very important [14,38,51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific characteristics of the environment during the pandemic were far less important than the opportunities for outdoor activity that they afforded. For instance, other studies mentioned that most first-time users reported that having access to outdoor spaces during COVID-19 was very important [14,38,51].…”
Section: Discussionmentioning
confidence: 99%
“…[ 16,19,21,[32][33][34] Importance of green spaces for a wide range of activities from exercise to birding and reported values related to reducing stress in a time of global chaos-respite and relaxation in a time of distress. [5,21,[35][36][37][38][39] Increase in the number of visitors to parks during the pandemic. [19,26,40] Access and abundance of green spaces have been proven to be an essential factor in the health and wellbeing of urban dwellers [41][42][43], and research shows us that gardens, parks, natural areas, and other types of open spaces provide many environmental and health benefits [44][45][46].…”
Section: Theme Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past three years, city and state administrators have been preoccupied with fighting the pandemic. Improvisations in public space reconfiguration have occurred on ad hoc basis, and some as informal projects by volunteer citizens ( Maury-Mora et al, 2022 ; Troya et al, 2020 ). We offer to city mangers an organized list of five most indicated urban innovations that would channel the emergent perspectives among the citizens for self-improvement as well as for becoming better citizens.…”
Section: Discussionmentioning
confidence: 99%
“…A las personas contactadas se les pidió que compartan con otros la encuesta, como una forma de muestreo de bola de nieve. Es decir, se utilizó una combinación de muestra por conveniencia y de bola de nieve, método utilizado por otros autores (Maury-Mora et al, 2022).…”
Section: Materiales Y Métodounclassified